THE DYNAMICS OF GENETIC VARIABILITY IN THREE GENERATIONS OF MASS SELECTION FOR FAST GROWTH IN AFRICAN CATFISH, Clarias gariepinus ASSESSED BY MICROSATELLITE MARKERS - Imron Imron; Bambang Iswanto; Huria Marnis; Rommy Suprapto; Narita Syawalia Ridzwan (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2015)
Selective breeding aiming at improving the performance of economically important traits acts by exploiting population’s phenotypic variance. Due to the relationship between phenotype and genotype, selection on phenotype may also affect the profile of genotype. This study was aimed to monitor the impact of three generations of mass selection for fast growth in African catfish, Clarias gariepinus, on genetic variability, assessed by microsatellite. A total of 350 fish representing four populations, namely a composite base population (G-0), selected lines of the first generation (G-1) to the third generation (G-3), were sampled. The samples were screened for their genetic diversity using five microsatellite loci1 namely cga01, cga02, cga03, cga05, and cga09. Several genetic parameters including number of allele (A), allelic richness (AR), observed (Ho) and expected (He) heterozygosity, and fixation index (Fis) were evaluated. The results showed that there was a slight increase in the value of diversity indices in the G-1 relative to the G-0 and to the other two generations. Among these parameters, the number of allele seemed to be the most sensitive parameter in detecting genetic changes. All populations experienced heterozygote deficit and positive fixation index indicating the phenomena of inbreeding. Overall, selection for growth for three generations in African catfish breeding program resulted in significant genetic differentiation between populations. Further, the level of genetic differentiation seemed to accumulate along with the number of generaton in breeding program. However, selection did not result in a decline in genetic diversity within population. A relatively short period of the program, along with the use a high number of broodstock (mating pairs) to produce each generation seems to be able to maintain the stability of genetic diversity of the population.